Arcangela TArabotti: Metaphysics and Politics - Santos Uriarte, Irati (Logos. Anales del Seminario de Metafísica, 2023)
Arcangela Tarabotti (1604-1652) was encloistered against her will in a Venetian convent by her father at the early age of 11. She was obliged to spent there her whole life. This imprisonment helped her to think about women as a meaningful and rational part of the humankind. In this essay, using two of her most important works (Paternal Tyranny and That Women are of the Human Race), I explore her notions of humanity, woman (created by God as matter and idea), liberty and salvation, and try to value them, as they deserve, as important contributions to the history of the philosophical thought.